Robust multi-responsive supramolecular hydrogel based on a mono-component host–guest gelator. Issue 25 (29th May 2018) - Cheng, Weinan; Zhao, Dongxu; Qiu, Yuan; Hu, Haisi; Wang, Hong; Wang, Qin; Liao, Yonggui; Peng, Haiyan; Xie, Xiaolin
Abstract : The multi-responsive behaviors and formation mechanism of a robust supramolecular hydrogel based on a mono-component host–guest gelator have been emphasized. Abstract : Supramolecular hydrogels have been widely investigated, but the construction of stimuli-responsive mono-component host–guest hydrogels remains a challenge in that it is still hard to balance the solubility and gelation ability of the gelator. In this work, three azobenzene-modified β-cyclodextrin derivatives with different alkyl lengths (β-CD-Azo-C n ) have been synthesized. The length of the alkyl chain dramatically influences the solubility and gelation ability of β-CD derivatives in water. Among these derivatives, β-CD-Azo-C8 possesses the lowest minimum gelation concentration (MGC). Based on the host–guest interaction between β-CD and azobenzene units in aqueous solution, which is confirmed by UV-visible and ROESY NMR spectra, the gelators self-assemble and further interwine into networks through the hydrogen bonds on the surface of β-CD cavities. Hydrogels formed by mono-component gelators can collapse under external stimuli such as heating, competition guests and hosts, and UV irradiation. When the concentration of the gelator is more than 8 wt%, the hydrogel exhibits good self-supporting ability with a storage modulus higher than 10 4 Pa. The gel–sol transition temperature of the hydrogel is near body temperature, indicating its potential applications in biological materials.